Metasomatic tourmaline in hybrid contact-bands between gneiss and peridotite in the Ulten zone of the Eastern Italian Alps: chemistry and boron isotopic composition - Marocchi, Marta; Marschall, Horst R.; Konzett, Jürgen; Tropper, Peter; Ludwig, Thomas; Mair, Volkmar; Bargossi, Giuseppe Maria (The Canadian mineralogist, 2011)
Ultramafic rocks in the Ulten Zone (UZ) high-pressure mélange, in the Eastern Italian Alps, embedded in crustal gneisses, preserve a series of metasomatic hybrid bands generated by infiltration of aqueous fluids. These hybrid bands at the peridotite-gneiss contact comprise phlogopite and anthophyllite with accessory zircon, apatite and allanite. Here, we report the rare occurrence of centimeter-sized crystals of metasomatic tourmaline in two different UZ outcrops, at Mt. Hochwart and Malga Preghena. Tourmaline has a dravite-uvite-rich composition and shows optical and chemical zoning, with slightly variable Ti, Ca and Fe contents. Secondary-ion mass spectrometry (SIMS) analyses provide information on the intragrain B-isotopic zonation of the grains, which is correlated with optical and chemical zoning. The range in δ11B is from −7.4 to +0.3‰ for the Mt. Hochwart tourmaline, generally with an isotopically lighter core and heavier rim. The δ11B range for Malga Preghena tourmaline is from +1.2‰ in the core to −3.9‰ in the rim. Variable proportions of fluids derived from both the local crustal gneisses and a subducting slab control the B-isotope composition in the metasomatic tourmaline from the UZ. Fluid mixing in hybrid crustal-ultramafic bands can be monitored by metasomatic tourmaline, which may also have a significant impact on the B isotope budget of the subducted slab and the slab-mantle interface.